The term structure of sovereign spreads in emerging markets: A calibration approach for structural models - Katia Rocha; Francisco Augusto Alcaraz García (Institute for Applied Economic Research (ipea), 2015)
This paper proposes a simple structural model to estimate the term structure of sovereign spreads and the implied default probability of a selected group of emerging countries, which accounts for more than 50% of the J. P. Morgan EMBIG index. The real exchange rate dynamics, modeled as a pure diffusion process, are assumed to trigger default event. By relaxing the hypothesis of market completeness, the calibrated model generates sovereign spread curves consistent with market data, giving average deviations below 30 (Mexico, Russia and Turkey) or 60 (Brazil) basis points over time. We show the robustness of the model and argue that the criticism of structural models for underestimating the magnitude of market spreads should be reconsidered. The results suggest that the market tends to overprice the spreads for Brazil, whereas for Mexico, Russia and Turkey the model reproduces the market behavior.
Keywords: G13; G15; F34; G33; 330